Perancangan Sistem Informasi Skrining Kesehatan Terintegrasi Menggunakan Microsoft Visual Studio 2019 di Puskesmas Panghegar - Achmad Alwan Alfarisi; Sali Setiatin (Publikasi Indonesia, 2022)
This research aims to produce an integrated health screening information system design by using Microsoft Visual Studio 2019 at puskesmas Panghegar. The research method used is qualitative with a descriptive approach. Data collection techniques used are interviews, observations, and literature studies. The research and development method used is the waterfall model. The tools used in the design process are Flowchart, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD). Based on the results of the study there are problems found, namely: (1) health screening forms have not been computerized systems (2) integrated health screening forms are often lost or damaged. Health Screening Information System to make it easier for officers in the screening process without any errors and to know the previous patient’s history when the patient comes back for treatment.